Dante and Mercy - Нембрини, Франко (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
The article presents an original view on the practice of reading of Dante’s “The   Divine   Comedy”  by   an   Italian   teacher   Franco   Nembrini.   The   author suggests an individualistic conception of reading centered on the reader’s personal experience as a basis for the interpretation of a text. Analyzing the theme of mercy in “The Divine Comedy”, the author draws an analogy between Beatrice and the Virgin Mary. Textual descriptions and comparison of the functions of these two figures lead to the conclusion that “mercy” is acentral theme of the whole poem that unites all three canticles.